Managing Employee Retention in Mergers and Acquisitions: A Systematic Review - Yustisia Kristiana; Andry Panjaitan; Vasco A. H. . Goeltom; Agustian Budi Prasetya (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2021)
Start-ups are companies that focus on problem solving through innovation. Mergers and acquisitions (M&A) are one of the development methods used to achieve growth. People who work in start-ups do so because they want to be part of a business that is entrepreneurial. When this is acquired, it may conflict with the preferences held. The purpose of this article is to assess the efficacy of start-up acquisition as a strategy, the relationship between psychological ownership and employee retention, and the human resource model for the integration stage in the context of M&A transactions. This systematic review demonstrates that each chosen recruitment strategy has its own set of challenges, requiring each organization to assess its own strengths and weaknesses. Psychological ownership is positively related to employee retention in the company which is obtained through direct and mediating effects of employee commitment and involvement. The integration stage as the most complex stage and determines the success of mergers and acquisitions needs attention for organizations engaged in the start-up sector.